Pengaruh Pembelajaran E-learning Berbasis Google Classroom Terhadap Kemampuan Berpikir Kritis Siswa - jirana jirana; Firdaus Firdaus; Inria Inria (SAINTIFIK, 2022)
This study aims to see the effect of google classroom based e-learning on students’ critical thinking skills. This research was an experiment research using a quantitative approach, the research design used in this study was a quasi experiment (Nonequivalent control group design). Sample selection used sampling jenuh, the instrument used in this study was a questionnaire of critical thinking skills. Data analysis was performed using descriptive tests and inferential statistical tests. The result of students’ critical thinking skills obtained in the descriptive test calculated in the amount of the experimental class was 78.78, while the control class was 66.63. This shows that the experiment class was 12.15 higher than the control class. This proves that there were differences in students’ critical thinking skills in the experiment class and the control class, while the (ttest) significance value of 0.000 was smaller than the significance level of 0.05. Thus it can be concluded that there was an influence on the use of google classroom based e-learning on the critical thinking skills of class XI MIA MAN 1 Majene students’.